Extremely low thermal conductivity and enhanced thermoelectric performance of polycrystalline SnSe by Cu doping. (1st April 2018) - Gong, Yaru; Chang, Cheng; Wei, Wei; Liu, Jiang; Xiong, Wenjie; Chai, Shuang; Li, Di; Zhang, Jian; Tang, Guodong
Abstract: Here, we systematically investigated the effect of Cu doping on the thermoelectric properties of SnSe prepared by hydrothermal synthesis. Low Cu doped content (x = 0.01) lead to enhanced electrical conductivity and power factor compared with reported polycrystalline SnSe. Nanoscale precipitates and mesoscale grains define all-scale hierarchical architectures to scattering phonons. Furthermore, Cu atomic point-defect scattering play an important role in reducing the lattice thermal conductivity. These two favorable factors lead to low lattice thermal conductivity as low as 0.2 Wm − 1  K − 1 at 873 K. This ultralow thermal conductivity results in a ZT of ~ 1.2 at 873 K in Cu0.01 Sn0.99 Se. Graphical abstract: Nanostructures and Cu atoms are introduced to obtain ultralow thermal conductivity for optimizing thermoelectric properties of polycrystalline SnSe.Image 2